Los instrumentos de gestión y su influencia en la calidad de la gestión educativa en las instituciones educativas secundarias de la zona urbana de Iquitos 2022 - Tananta Gil, Rina (2024)
Results are presented in relation to the research that was formulated as a research question: How do Management Instruments influence the Quality of Educational Management of Secondary Educational Institutions in the urban area of Iquitos, 2022? The hypothesis was that the Management Instruments are significantly linked to the Quality of Educational Management, of the Secondary Educational Institutions of the urban area of Iquitos, 2022, and to determine the significant relationship of the Management Instruments with the Quality of Educational Management, of the Secondary Educational Institutions of the urban area of Iquitos, 2022. was set as an overall objective. The type of research is applied with a correlational descriptive design, 400 teachers and 19 principals made up the population and the sample was 119. The resulting information obtained using Spearman's non-parametric rho test with a significance level of 0.05, which allows us to show that management instruments influence the quality of educational management in secondary level level institutions in the urban area of Iquitos. 2022 (rho = 0.874), a significance level of 0.000 (p0.05) implies that there is a statistically significant relationship between the variables.